Virgin Coconut Oil Therapy for Coastal Dermatitis: A Community Nursing Application of Orem's Self-Care Deficit Theory - Galuh Harini Sasiraya; Evy Aristawati; Apriana Rahmawati; Sri Wahyuni (Inovasi Lokal, 2026)
Dermatitis is one of the most common integumentary disorders encountered in community nursing practice, and its burden is amplified among populations continuously exposed to environmental irritants such as seawater, wind, dust, and extreme humidity. Coastal communities sit at the upper end of this exposure gradient, yet affordable, theory-guided non-pharmacological interventions for this population remain sparsely evaluated. This study evaluated the effectiveness of standardized topical Virgin Coconut Oil (VCO) therapy, delivered through a structured nursing process guided by Orem's Self-Care Deficit Theory, on impaired skin integrity among coastal residents with contact dermatitis. A quasi-experimental, one-group pretest-posttest design, reported in accordance with the TREND Statement, was conducted over three consecutive days (12–14 May 2026) with two purposively selected participants, aged 35 and 60 years, in the coastal working area of the Gadingrejo Community Health Center, Pasuruan City, Indonesia. VCO was applied topically per a standard operating procedure while nursing support progressed from a wholly compensatory to a partially compensatory and finally a supportive-educative system. Skin integrity was assessed daily using SDKI/SLKI-aligned indicators covering pruritus, erythema, skin texture, lesion status, and local skin temperature. Both participants showed a consistent decline in pruritus and erythema, smoother skin texture, and reduced local skin temperature (37.4°C to 36.5°C in the older participant), with near-complete symptom resolution by the third day. Structured VCO therapy delivered through a theory-guided nursing process meaningfully restored skin integrity within 72 hours and moved participants toward independent self-care, supporting its viability as a low-cost, evidence-based community nursing intervention for coastal dermatitis.